2010
DOI: 10.1007/s10194-010-0191-6
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between headache and epilepsy in a pediatric headache center

Abstract: The purpose of this study was to analyse the comorbidity between headache and epilepsy in a large series of children with headache (1,795). Fifty-six cases (3.1%) suffered from idiopathic headache and idiopathic or cryptogenic epilepsy or unprovoked seizures. There was a strong association between migraine and epilepsy: in migraineurs (46/56) the risk of epilepsy was 3.2 times higher when compared with tension-type headache, without significant difference between migraine with and without aura (P = 0.89); chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 26 publications
7
78
1
2
Order By: Relevance
“…Moreover, this finding has been also confirmed by other studies (17,18). In another study, Toldo et al documented that epilepsy is 3.2 times higher than in migrainous patients and they did not find the same association with tension type headache and the difference between migraine with and without aura in this regard (19).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, this finding has been also confirmed by other studies (17,18). In another study, Toldo et al documented that epilepsy is 3.2 times higher than in migrainous patients and they did not find the same association with tension type headache and the difference between migraine with and without aura in this regard (19).…”
Section: Discussionmentioning
confidence: 90%
“…In a pediatric population, there was no correlation between IIH and PIH and no tendency for children with IIH migraine to have migrainous PIH [9] . Similarly, another study reported that children with migraine did not increase the risk of PIH than the children with tension-type headache [11] . Interestingly, no association has been found between family history of headaches or migraine and PIH.…”
Section: Agementioning
confidence: 86%
“…However, some studies that addressed pediatric population found a lower prevalence of PIH (12-36%) [9,11,12] than in most adult studies (30-52%) [13,14] . In 2011, Verrottiet al conformed [15] a cross-sectional multi-center study, which includes 1,264 epileptic children.…”
Section: Agementioning
confidence: 98%
See 1 more Smart Citation
“…The prevalence of migraine in populations of individuals with epilepsy is estimated as 8-24% (Toldo et al, 2010), so that the risk of migraine is approximately twice that in the normal population (Ottman & Lipton, 1994).…”
Section: Discussionmentioning
confidence: 99%